2017
DOI: 10.1016/j.tem.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Role of AHR and HIF-1α in Glioblastoma Metabolism

Abstract: Glioblastoma (GBM) progression is associated with metabolic remodeling in both glioma and immune cells, resulting in the use of aerobic glycolysis as the main source energy and biosynthetic molecules. The transcription factor HIF-1α drives this metabolic reorganization. Oxygen levels as well as other factors control the activity of HIF-1α. In addition, the ligand-activated transcription factor AHR modulates tumor-specific immunity and can also participate in metabolic remodeling. AHR activity is regulated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 95 publications
(129 reference statements)
1
67
0
Order By: Relevance
“…Our present study proved that Gen could protect H9c2 cells from CoCl 2 -induced hypoxic injury. Hypoxia is a well-characterized trigger of HIF-1α-dependent signaling [33]. The activation of HIF-1α has been revealed in human hearts under conditions of myocardial hypoxia and infarction [34].…”
Section: Discussionmentioning
confidence: 99%
“…Our present study proved that Gen could protect H9c2 cells from CoCl 2 -induced hypoxic injury. Hypoxia is a well-characterized trigger of HIF-1α-dependent signaling [33]. The activation of HIF-1α has been revealed in human hearts under conditions of myocardial hypoxia and infarction [34].…”
Section: Discussionmentioning
confidence: 99%
“…Cariporide treatment has been shown to reduce NHE1 mRNA and protein expression in isolated rat renal cortex 46 . Glioma hypoxic microenvironment and acidosis stimulate the HIF-1α expression 47 , 48 , which may result in upregulation of NHE1 expression and promote the acidic microenvironment 49 51 . Therefore, inhibition of NHE1 activity with HOE642 could relieve the acidic, hypoxic microenvironment and reduce HIF-1α expression, leading to the downregulation of NHE1 protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we performed bioinformatic analysis on RLIP76 coexpressed genes from the TCGA GBM database and found that RLIP76 plays a crucial role in the reduction of oxidative phosphorylation and ubiquitinmediated proteolysis in GBM. It has been well documented that the ubiquitin-and proteasome-mediated degradation of HIF-1α plays a pivotal role in enhanced glycolysis in GBM [37]. Under hypoxic conditions, HIF-1α can escape ubiquitin-mediated proteolysis by disassociating with VHL, a component of an E3 ubiquitin-protein ligase complex [38].…”
Section: Discussionmentioning
confidence: 99%